A new species of Ilyobius Enderlein, 1910 (Megaloptera: Sialidae) from a threatened region in the Mantiqueira Mountain range (Brazil) - Mendes, Gabriela Caroline; Nascimento, Jeane Marcelle Cavalcante Do; Fusari, Lívia Maria; Santos, Mireile Reis Dos; Hamada, Neusa (Zootaxa, 2022)
A new species of Ilyobius Enderlein, 1910 (Megaloptera: Sialidae) from the Brazilian Atlantic Forest is described based on male, female, and larva. Ilyobius erebus sp. nov. is the 11th species in this genus, and the fourth reported in Brazil. In addition, male and female genitalia of I. hauseri (Contreras-Ramos, Fiorentin & Urakami, 2005) are redescribed based on the holotype and newly collected specimens at the type locality. Based on the current classification system, I. erebus sp. nov. is placed in the I. chilensis group, which was supported by male and female genital structures. The type locality of the new species is threatened by human impacts, and conservation of its habitat is needed.